Halochlorella Rubescens Cultivation In Photobioreactors For Optimum Lipid Production - Anbalagan, Lavanya (2022)
Lipids from microalgae have been studied for their potential application in various industries. The microalgae lipid production is mainly influenced by the cultivation methods and environmental conditions. This study investigates the effects of lipid content and lipid formation kinetics at different cultivation conditions involving pH, combination of nitrogen and phosphorus sources of different concentrations, carbon dioxide concentrations and light intensity on Halochlorella rubescens, a freshwater microalgae in photobioreactors with different configurations such as the cubic tank photobioreactor (CTPBR), centralized light photobioreactor (CLPBR) and tubular photobioreactor (TPBR) using one variable at a time (OVAT) method. The significance of differences between each test variable was determined using one way ANOVA where (p ˂ 0.05) is considered statistically significant. Qualitatively the lipid accumulation of cells was determined via Nile red staining method. The analysis of Fourier Transform Infrared Spectroscopy (FTIR) at different parameters confirmed the functional groups of lipids. The Leudeking-Piret model revealed that the lipid production of Halochlorella rubescens is growth-associated at all different cultivation conditions. The highest lipid content (39.42 ± 0.426%) and maximum biomass density (0.3662 ± 0.002 gL-1) was achieved at optimized conditions (pH 9, nitrogen-depleted medium, 15% CO2, 4000 lux) in 10L volume using TPBR.